Prognostic Value and Biological Role of miR-126 in Breast Cancer - Soofiyani, Saiedeh R.; Hosseini, Kamran; Ebrahimi, Tahereh; Forouhandeh, Haleh; Sadeghi, Mohammadreza; Beirami, Sohrab Minaei; Ghasemnejad, Tohid; Tarhriz, Vahideh; Montazersaheb, Soheila (MicroRNA, 2022)
In eukaryotic organisms such as humans, some noncoding single-stranded RNAs (ncRNAs) contribute to regulating the expression of some genes before and after the transcription process, which in turn controls a number of vital physiological processes, including cell proliferation, differentiation, invasion, angiogenesis, and embryonic development. miR-126 is one of these miRNAs expressed exclusively in endothelial cells such as capillaries and vessels involved in controlling angiogenesis. In recent years, the link between miRs such as miR-126 and the pathology of breast cancer has attracted the attention of many researchers. Numerous studies have shown that miR-126 may be able to suppress tumor tissue metastasis or to increase tumor metastasis through complex molecular mechanisms. There is ample clinical evidence that miR-126 can be used as a biomarker to predict and diagnose breast cancer due to the increased or decreased expression of certain genes in breast cancer tissue. In this review, we discuss the association between the growth and metastasis (tumorigenesis) of breast cancer and miR-126, as well as the relationship between current research advances in the prognosis, diagnosis, and treatment of breast cancer and miR-126.
Keywords: diagnosis